The impact of Personality traits on Code-Switching Frequency in Saudi Arabia: A Mediating role of Adaptive Communication - Albahoth, Zakria Mohammed; Jabar, Mohd Azidan bin Abdul; Jalis, Farhana Muslim Binti Mohd (Dirasat: Human and Social Sciences, 2025)
Objectives: The research explores how personal traits influence adaptive communication behaviors and code-switching frequency by focusing on the big five personality traits (openness, consciousness, extraversion, agreeableness, and neuroticism). Methods: To obtain the aim of the present study, we gathered data from 448 respondents using closed questionnaire, we tested the hypotheses using structural equation modeling through Smart PLS software. Results: The empirical findings reveal positive associations between personality traits (i.e., openness, consciousness, extraversion, agreeableness, and neuroticism) and communication accommodation, emphasizing individuals' ability to adjust communication styles in diverse social and linguistic contexts. The study uncovers a positive relationship between communication accommodation and code-switching frequency, highlighting the frequency with which individuals switch between languages or dialects. Notably, communication accommodation mediates the relationship between personality traits (i.e., openness, consciousness, extraversion, agreeableness, and neuroticism) and code-switching frequency. Conclusions: this study provides valuable insights into the association between personality traits, communication accommodation, and code-switching, offering practical applications and contributing to the evolving discourse on effective and adaptive communication in diverse environments.